(untitled) (Research, Society and Development, 2020)
The components present in some foods have the ability to directly influence the health-disease process through epigenetic molecular mechanisms, reducing the risk of developing some diseases, especially Chronic Non-Communicable Diseases (NCDs), such as cancer. In this sense, the present study seeks to elucidate the role of some nutrients and bioactive compounds in food in epigenetic modulation as a way of preventing and fighting cancer. For that, a systematic search was performed in the LILACS, PubMed and BVS databases. The descriptors were used: Epigenomics, Phytochemical Compounds, Neoplasms and Nutrients, all selected according to the Health Sciences Descriptors and used in the languages: Portuguese and English. Initially, 3177 publications were found and after applying the predefined inclusion and exclusion criteria, nine relevant publications remained for the construction of the work. It was verified from the selected literature, that some nutrients and bioactive compounds, such as Curcumin from the turmeric, Sulforaphane and Phenethyl Isothiocyanate (PEITC) from cruciferous vegetables, Resveratrol (RES) from red grapes and wine, β-carotene from orange vegetables, Vitamin C from citrus fruits and some phytochemicals, such as Quercetin and Caffeic acid, play an important role in fighting cancer, as, among other benefits, they can epigenetically stimulate the gene expression of factors preventive measures, but they can also inhibit the expression of factors linked to metastasis and progression of the pathology already installed. Finally, it is clear that the influence that some foods have on gene expression and represents an important tool against cancer, especially in relation to prevention. However, it is necessary to carry out more detailed studies in relation to doses and possible harmful effects.